Peran Etika Komunikasi Dalam Konteks Pemilihan Umum Tahun 2024: Kajian Etika Kristen - Belo, Yosia; S., Rika (STT Pelita Dunia, 2023)
Abstract: The 2024 General Election or General Election is a democratic celebration for the Indonesian nation which will be held simultaneously (election of president, legislative members and regional heads). So the potential for conflict or failure will be wide open. This potential becomes a logistics when reflecting on the 2019 elections, where there was a lot of spreading hatred, hoax news and even slander and violations on social media. That is why, this research focuses on the ethical role of communication in elections from a Christian ethical perspective. Therefore, even though the number of Christian voters is a minority, their position is also very urgent and strategic. Researchers use qualitative methods with emphasis on literature review and analysis. As a result of the research, three important roles of communication ethics in the 2024 Election were obtained, namely: communication ethics will produce cool and religious communication during the 2024 Election, communication ethics will reduce the spread of hatred, hoax news, and slander spread massively during the 2024 Election, and ethics Communication will create peaceful and conducive elections. Abstrak: Pemilu atau Pemilihan Umum 2024 merupakan pesta demokrasi bagi bangsa Indonesia yang dilaksanakan secara serentak (pemilihan presiden, anggota legislatif dan kepala daerah), sehingga potensi untuk terjadinya konflik atau perselisihan akan terbuka lebar. Potensi ini menjadi logis apabila berkaca pada Pemilu tahun 2019, di mana banyak menyebar ujaran kebencian, berita-berita hoaks hingga fitnah dan penghinaan di media sosial. Itulah sebabnya, penelitian ini bertujuan untuk menunjukkan peran etika komunikasi dalam Pemilu ditinjau dari perspektif etika Kristen. Oleh karena itu, sekalipun jumlah pemilih Kristen adalah minoritas, namun posisinya juga sangat urgen dan strategis. Peneliti menggunakan metode kualitatif dengan menitikberatkan pada kajian dan analisis pustaka. Hasil penelitian menunjukkan tiga peran penting etika komunikasi dalam Pemilu 2024, yakni: etika komunikasi akan menghasilkan komunikasi yang sejuk dan religius selama Pemilu 2024, etika komunikasi akan meredam tersebarnya ujaran kebencian, berita hoaks, hingga fitnah menyebar secara masif selama Pemilu 2024, dan etika komunikasi akan menciptakan Pemilu yang damai dan kondusif.